More gray, more volatile? - Baksa, Daniel,Munkacsi, Zsuzsa (International Monetary Fund, 2019)
The evidence on the inflation impact of aging is mixed, and there is no evidence regarding the volatility of inflation. Based on advanced economies' data and a DSGE-OLG model, we find that aging leads to downward pressure on inflation and higher inflation volatility. Our paper is also the first, using this framework, to discuss how aging affects the transmission channels of monetary policy. We are also the first to examine aging and optimal central bank policies. As aging redistributes wealth among generations and the labor force becomes more scarce, our model suggests that aging makes monetary policy less effective and in more gray societies central banks should react more strongly to nominal variables
10.5089/9781513509082.001
Keywords: Graue Literatur; Banks and Banking; Demography; Economics of the Elderly; Economics of the Handicapped; Non-labor Market Discrimination; Price Level; Deflation; Macroeconomics: Consumption; Saving; Wealth; Interest Rates: Determination; Term Structure; and Effects; Demand and Supply of Labor: General; Monetary Policy; Demographic Trends; Macroeconomic Effects; and Forecasts; Macroeconomics; Population & demography; Finance; Labour; income economics; Aging; Inflation; Consumption; Real interest rates; Labor supply; Population and demographics; National accounts; Financial services; Labor; Population aging; Prices; Consumption; Economics; Interest rates; Labor market; aging; monetary policy transmission; optimal monetary policy; inflation targeting